The Relevance Of The Development Of Network Marketing In The Modern Economy - Musayeva Shoira Azimovna (Genius Publishing Group, 2022)
This article considers the task of network marketing is the information coverage of the maximum coverage of people. Selling is a natural result of this outreach. Turnover in network marketing arises and is maintained due to the fact that people inform about the company's products
Keywords: Marketing; trade; factor; people